THE INFLUENCE OF WORK TRAINING, COMPETENCE AND DISCIPLINE OF WORK ON EMPLOYEE PERFORMANCE IN PT. LESTARINDO PERKASA - Raniasari Bimanti Esthi; Inggritz Savhira (Kusuma Negara Business School, 2019)
The development of increasingly sophisticated technology requires all people to be able to follow these developments, not least the human resources in a company. These changes require individuals to think creatively, work fast, and be right to be a person who is able to compete. In addition, job training, competence and work discipline in an organization are also things that can affect employee performance. This study aims to determine how much influence the job training, competence and work discipline on employee performance at PT. Lestarindo Perkasa. This type of research is quantitative. With a population of employees at PT. Lestarindo Perkasa and sampling with saturated sampling techniques with a total sample of 75 respondents. For data collection including observation, questionnaire distribution and study of literature. The analytical methods used are validity test, reliability test, classic assumption test, multiple linear analysis and hypothesis testing. T test results showed that the t value was 2.028 with a significant value of 0.046 which means that the first hypothesis was accepted and partially showed that there was a positive and significant influence between job training on employee performance. The competency variable obtained the results of the t test with a calculated t value of 2.812 and a significant value of 0.006 which means that the second hypothesis was accepted and showed that there was a positive and significant effect between competencies on employee performance. Work discipline variables obtain the results of t test with a calculated value of 2.159 and a significant value of 0.034, which means the third hypothesis is accepted and shows that there is a positive and significant influence between work discipline on employee performance and it can be concluded that the contribution of work training, competence and work discipline to employee performance together is 34.7% while the remaining 65.3% is influenced by other variables not included in this study at PT. Lestarindo Perkasa.